2006
DOI: 10.1115/1.2354530
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds Stress Model in the Prediction of Confined Turbulent Swirling Flows

Abstract: Strongly swirling vortex chamber flows are examined experimentally and numerically using the Reynolds stress model (RSM). The predictions are compared against the experimental data in terms of the pressure drop across the chamber, the axial and tangential velocity components, and the radial pressure profiles. The overall agreement between the measurements and the predictions is reasonable. The predictions provided by the numerical model show clearly the forced and free vortex modes of the tangential velocity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 20 publications
0
22
0
2
Order By: Relevance
“…The results simulated using the RSM model are closer to the results obtained by the SST k-ω model. Moreover,[5,24,25,26] have observed that the RSM can predict flow features in the swirling flows to a reasonable accuracy and have validated their simulations by experiments. Thus, a good comparison with RSM implies that the SST k-ω model can predict the flow features accurately.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The results simulated using the RSM model are closer to the results obtained by the SST k-ω model. Moreover,[5,24,25,26] have observed that the RSM can predict flow features in the swirling flows to a reasonable accuracy and have validated their simulations by experiments. Thus, a good comparison with RSM implies that the SST k-ω model can predict the flow features accurately.…”
mentioning
confidence: 85%
“…Considering that a large number of simulations are needed to quantify the influence of different diode geometries and operating conditions (and an absence of any evidence of superiority of LES over RANS for simulating flow in a vortex diode), we have used the RANS approach in this work. The RANS has been shown to perform adequately for the confined vortex flows [5][6][7][24][25][26].…”
Section: A) Turbulence Modelmentioning
confidence: 97%
“…The model relaxes the local equilibrium assumption (production = dissipation) that is adopted by the standard wall function at neighboring cells. Many studies have shown that the KEMs or RSM with non-equilibrium wall functions can provide the best predictions for complex flows [20,36]. Therefore, a non-equilibrium wall function is adopted in the present research.…”
Section: Turbulence Modelmentioning
confidence: 98%
“…Experimental and analytical study of the pressure drop across a double-outlet vortex chamber using a single generator has been done by Jawarneh et al [25]. A numerical study to predict the confined turbulent swirling flows using Reynolds stress model has been performed by Jawarneh and Vatistas [26].…”
Section: Introductionmentioning
confidence: 99%